PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN PENGETAHUAN AWAL TERHADAP HASIL BELAJAR BIOLOGI SISWA SMA 1 SOLOK SELATAN - Yoko Masna Rivan; M. Yulia Ratna Sari (LPPM Universitas Cipta Mandiri, 2024)
This research is motivated by the low learning outcomes of biology, which is due to the ongoing learning is still dominated by educators, students are less motivated and bored with the learning activities carried out. Educators have not been able to encourage students to develop their individual talents and skills, and students have not been able to formulate their own hypotheses. Because learning is not optimal, efforts are needed to improve biology learning outcomes. This study aims to reveal the effect of the CTL learning model and prior knowledge on the biology learning outcomes of the tenth graders of SMA 1 Solok Selatan. The research design used was Randomized Group Only Design. The research population was all students of class X SMA 1 Solok Selatan for the 2023/2024 academic year. The sample in this study was selected by purposive sampling, selected class X4 as the control class and class X2 as the experimental class. Data were collected through preliminary knowledge tests and learning outcomes tests. The results of data analysis revealed: (1) Biology learning outcomes of students taught with Contextual Teaching and Learning (CTL) learning models were significantly higher than students learning outcomes taught using conventional learning models, (2) Biology learning outcomes of students with high prior knowledge taught by the Contextual Teaching and Learning (CTL) learning model significantly higher than the biology learning outcomes of students with high prior knowledge taught by conventional learning models (3) Biology learning outcomes of students with low prior knowledge who being taught using the Contextual Teaching and Learning (CTL) learning model is significantly higher than the biology learning outcomes of students with low prior knowledge who are taught using the conventional learning model, (4) There is no interaction between the learning model and prior knowledge regarding adapt students' biology learning outcomes.